Editorial Preface - Ab Gani, Muhamad Abdul Aziz; Ramli, Ishak (Idealogy Journal; Vol 5 No 2 (2020): Idealogy Journal (September 2020)DO - 10.24191/idealogy.v5i2.281, 2020)
Overview of the Idealogy of Arts and Social Science by the Chief and Deputy Chief Editor.